Assessment of cement replacement with fine recycled rubber particles in sustainable cementitious composites - Atef Mohamed (De Gruyter, 2021)
Egypt plays an important role in the consuming markets for tires all over the world. There is an urgent need to get rid of them in an economic and environmental way since it is considered as a harmful waste if burnt. The World trend is directed towards the improvement of new techniques to insert the rubber into useful products to maximize the benefit of recycling. This research deals with the expansion of novel techniques for rubber powder recycling for various purposes in a robust construction. Recycled rubber particles (RRP) are mixed with ordinary Portland cement (OPC) using various water to binder ratio (W/B) at 0.3 and 0.4. The Fourier transform – infrared (FT-IR) spectra is measured for RRP. The compressive strength (C.S) is investigated for the rubberized cement pastes at 1, 3, 7, 14 and 28 days. The results aimed to enhance the compressive strength of rubberized cement pastes through improving the bonding strength between RRP and OPC by using fine particles of RRP. Maintaining the compressive strength in the highest levels with different RRP percentages in addition to the vibrational damping property of RRP gives rubberized cement pastes the advantage to replace ordinary concrete in most construction applications.